Role of Sulphur nutrition in oilseed crop production - A review - Harmandeep Singh Chahal,; Amanpreet Singh,; Gurdeep Singh Malhi, (Journal of Oilseed Brassica, 2026)
Sulphur is an essential nutrient for the production of oilseeds. It is the 13th most abundant element in the earth’s crustwith an average concentration of 0.06 percent. It is necessary for the synthesis of proteins, oils, and vitamins. Agriculturalsoils have a low concentration of inorganic sulfur compared to the organic form. A sulfur deficiency also leads to a 40percent reduction in the quality and quantity of rapeseed or oilseeds. Sulfur deficiency is becoming very common inmany states of India. In previous years, various studies on sulfur have been carried out, viz. factors that affect theavailability of Sulphur to plants, its function in the plant, the response of Sulphur in various crops, etc. The objective ofthis review is to provide an update on recent discoveries related to these topics, which may contribute to a betterunderstanding of S fertilization and the role of S in oilseeds.